2000
DOI: 10.1046/j.1365-2648.2000.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sorrow in parents of children with newly diagnosed diabetes: a review of the literature and discussion of the implications for nursing practice

Abstract: Childhood (type 1) diabetes is a chronic, life-long condition, the diagnosis of which may represent multiple losses for parents. Their emotional responses to the diagnosis have been likened to the grief reactions experienced as a result of bereavement through death. The practice of health professionals who work with these families is informed by two contrasting theoretical views of the progress of grief reactions; the time bound and the chronic sorrow perspectives. This paper provides a critical appraisal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 37 publications
4
38
0
2
Order By: Relevance
“…The concept "loss" is described in literature mostly in related terms as sadness, stress, distress, grief, chronic sorrow, bereavement and mourning (Corr et al 2000;Lowes and Lyne 2000). Loss in our study matches closely with the concept analysis of Robinson and McKenna (1998).…”
Section: Discussionsupporting
confidence: 84%
“…The concept "loss" is described in literature mostly in related terms as sadness, stress, distress, grief, chronic sorrow, bereavement and mourning (Corr et al 2000;Lowes and Lyne 2000). Loss in our study matches closely with the concept analysis of Robinson and McKenna (1998).…”
Section: Discussionsupporting
confidence: 84%
“…However, our study also points to parents’ experiences of the impossibility of being fully confident in the task of regulating the child’s blood glucose. In Lowes and Lyne (2000), the life-changing character of the situation of having a child with T1D was also underscored. Parents were interviewed at the first week, 4 months and 12 months after the diagnosis, and it was found that it took about 12 months to find a new way of living.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasised parental psychological distress when and immediately after a child is diagnosed with T1D (Landolt, Vollrath, Laimbacher, Gnehm, & Sennhauser, 2005; Lowes & Lyne, 2000; Stallwood, 2005; Streisand et al, 2008). Symptoms such as shock and sorrow (Lowes & Lyne, 2000), post-traumatic stress disorder (Landolt et al, 2005) and increased anxiety and depression levels (Streisand et al, 2008) are common among parents of children newly diagnosed with diabetes. To learn to give your own child injections and finger pricks could be both a practical and an emotional challenge for parents.…”
Section: Introductionmentioning
confidence: 99%
“…The peri-diagnostic period is often a distressing time for parents and children and represents the starting point for a complex relationship between a chronically ill child and their parents. Furthermore during this period, clinicians, children and parents are deciding optimal treatment and management regimens (Lowes & Lyne, 2000;Valentine & Lowes, 2008). Often, clinicians rely on reports of child health-related quality of life (HRQL) to facilitate patient-clinician communication, improve child/parent satisfaction, and to aid in clinical decision-making (Varni, Limbers, & Burwinkle, 2007).…”
Section: Introductionmentioning
confidence: 99%